2012
DOI: 10.1186/1471-2377-12-142
|View full text |Cite
|
Sign up to set email alerts
|

Prospective memory tasks: a more sensitive method for screening cognitive impairment in ALS?

Abstract: BackgroundCognitive change is prevalent in patients with amyotrophic lateral sclerosis (ALS), but still lack a widely accepted and sensitive screening method. In this study, we try to find a sensitive screening battery for detecting subtle cognitive deficits in patients with ALS.MethodsEighty consecutive ALS patients and 57 matched normal controls underwent the Mini-Mental Status Examination (MMSE), the verbal fluency test (VFT), the Stroop Color Word Interference Test (CWT), and the prospective memory (PM) te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 31 publications
0
4
1
Order By: Relevance
“…Previously, some studies have found that people with bulbar onset of ALS are more likely to have cognitive impairment than those with spinal onset [39,53,54], but others do not [33,35,55]. In our study, the site of onset had no effect of the presence of cognitive impairment as determined by the ACE-III, but site of onset influenced cognitive impairment based on FAB logistic regression results.…”
Section: Accepted Manuscriptcontrasting
confidence: 38%
“…Previously, some studies have found that people with bulbar onset of ALS are more likely to have cognitive impairment than those with spinal onset [39,53,54], but others do not [33,35,55]. In our study, the site of onset had no effect of the presence of cognitive impairment as determined by the ACE-III, but site of onset influenced cognitive impairment based on FAB logistic regression results.…”
Section: Accepted Manuscriptcontrasting
confidence: 38%
“…The PM assessment paradigm is derived from the standard Chinese version of the PM test designed by Einstein and McDaniel 50,51 . The details of this paradigm have been described previously 52 . We revised some details according to the actual situation of schizophrenic patients to facilitate the subject's operation.…”
Section: Methodsmentioning
confidence: 99%
“… 50 , 51 The details of this paradigm have been described previously. 52 We revised some details according to the actual situation of schizophrenic patients to facilitate the subject's operation. The test was divided into two parts to assess TBPM and EBPM, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Memory dysfunction in ALS has been associated with the impaired integrity of core brain structures, including the hippocampus(Raaphorst et al, 2015), fornix (Sarro et al, 2011) and uncinate fasciculus (Christidi et al, 2014). Impaired prospective memory (Ji, Wei, Chui, Wang, & Fan, 2012), working memory (Hammer, Vielhaber, Rodriguez-Fornells, Mohammadi, & Munte, 2011) and recall of emotionally salient material (Cuddy, Papps, Thambisetty, Leigh, & Goldstein, 2012; Papps, Abrahams, Wicks, Leigh, & Goldstein, 2005) have also been identified in ALS. However, no studies to date have investigated personally relevant memory recall in ALS.…”
mentioning
confidence: 99%